Static stability test and simulation of a large-scale modular carbon fiber reinforced polymer wheel-spoke-shaped stiffening ring subjected to multi-point radial loading. (15th June 2023) - Li, Shiping; Mi, Xiang; Chen, Longlong; Jianhui, Hu; Zhao, Bing; Zhang, Yibei; Chen, Wujun
Highlights: A new large-scale modular CFRP wheel-spoke-shaped stiffening ring is proposed. A CFRP wheel-spoke-shaped stiffening ring with a diameter of 40.0 m was integrated through modular assembly technology. The buckling failure position and buckling load of the CFRP wheel-spoke-shaped stiffening ring are determined by a multi-point loading static stability test. A refined multi-layered shell model based on the combined eigenmode imperfection method is proposed and established. Abstract: To enhance the hoop stiffness of the rigid-flexible integrated airship, a new large-scale wheel-spoke-shaped stiffening ring composed of modular carbon fiber reinforced polymer (CFRP) standard trusses was designed in this work. Particularly, by using the modular assembly technology, the CFRP stiffening ring with a diameter of 40.0 m was integrated assembly, which verified the feasibility of the proposed structural design method. Based on the applied uniformly distributed load form of the CFRP wheel-spoke-shaped stiffening ring during the flight of the rigid-flexible integrated airship, the standard truss module was subjected to a multi-point loading static stability test through a self-developed loading device, while the in-plane buckling failure position and buckling load of the CFRP wheel-spoke-shaped stiffening ring were also determined. Based on the refined multi-layered shell model, the combined eigenmode imperfection method was used for the nonlinear buckling analysis of the CFRP truss module. The buckling failure mode and the buckling load obtained from the simulation results were in good agreement with the test results. The proposed and verified large-scale modular CFRP wheel-spoke-shaped stiffening ring improved the hoop stiffness of the rigid-flexible integrated airship and achieved structural weight reduction and the design goal of the large-scale structure. The refined multi-layered shell model based on the combined eigenmode imperfection method has an important application value and guiding significance for investigating the buckling property of CFRP wheel-spoke-shaped stiffening rings, which provides valuable technical support for the structural design of rigid-flexible integrated airships.